Lesion network localization of free will - Darby RR; Joutsa J; Burke MJ; Fox MD (NATL ACAD SCIENCES, 2022)
Our perception of free will is composed of a desire to act (volition) and a sense of responsibility for our actions (agency). Brain damage can disrupt these processes, but which regions are most important for free will perception remains unclear. Here, we study focal brain lesions that disrupt volition, causing akinetic mutism (n = 28), or disrupt agency, causing alien limb syndrome (n = 50), to better localize these processes in the human brain. Lesion locations causing either syndrome were highly heterogeneous, occurring in a variety of different brain locations. We next used a recently validated technique termed lesion network mapping to determine whether these heterogeneous lesion locations localized to specific brain networks. Lesion locations causing akinetic mutism all fell within one network, defined by connectivity to the anterior cingulate cortex. Lesion locations causing alien limb fell within a separate network, defined by connectivity to the precuneus. Both findings were specific for these syndromes compared with brain lesions causing similar physical impairments but without disordered free will. Finally, our lesion-based localization matched network localization for brain stimulation locations that disrupt free will and neuro-imaging abnormalities in patients with psychiatric disorders of free will without overt brain lesions. Collectively, our results demonstrate that lesions in different locations causing disordered volition and agency localize to unique brain networks, lending insight into the neuroanatomical substrate of free will perception.